Pencegahan serta Penanganan Kekerasan Seksual pada Universitas Sultan Ageng Tirtayasa dalam Lingkup Implementasi Kebijakan - Salwa Azzahra; Leo Agustino; Sierfi Rahayu (Epistemik Press, 2024)
This study focuses on the implementation of the Sexual Violence Prevention and Handling policy carried out at Sultan Ageng Tirtayasa University referring to the Regulation of the Chancellor of Sultan Ageng Tirtayasa University Number 5 of 2021 concerning PPKS in the Untirta Environment. The problems studied in this study are the many cases of sexual violence that still occur in Untirta, campus facilities are not fully available to support anti-sexual violence, the implementation of socialization has not reached all target groups, and the culture of the target group still considers sexual violence as a taboo to report. The purpose of this study is to determine how the policy of preventing and handling sexual violence is implemented at Sultan Ageng Tirtayasa University. This study uses the theory put forward by Van Metter and Van Horn. The researcher used a descriptive qualitative method with data analysis through interviews, observations, documentation, and literature studies. For the selection of informants, the researcher used purposive and snowball techniques. The results of this study indicate that implementing the Prevention and Handling of Sexual Violence policy at Sultan Ageng Tirtayasa University has been carried out quite well because it meets each variable studied in the Van Metter Van Horn theory. However, in its implementation, there are certainly still various obstacles faced by the Untirta PPKS Task Force.